Making Google Congestion Control robust over Wi-Fi networks using packet grouping - Gaetano Carlucci; Luca De Cicco; Stefan Holmer; Saverio Mascolo (Proceedings of the 2016 Applied Networking Research Workshop, 2016)
Google congestion control (GCC) has been proposed for the case of delay sensitive traffic (i.e. video-conference) in the WebRTC framework. In this paper we analyze the effect of wireless channel outages on the GCC. We have observed that, when a channel outage ends, there are packets that arrive at the receiver as a burst. This behavior impairs the delay-based controller employed by GCC, resulting in throughput degradation. We propose a solution to make GCC robust with respect to channel outages. In particular, by grouping packets that arrive in a burst, the delay-based controller avoids to misinterpret a burst as network congestion. In order to prove the effectiveness of the proposed solution we have carried out a trace-driven experimental evaluation in a loaded Wi-Fi scenario.
Keywords: Wi-Fi; WebRTC; Congestion control